Dielectrophoretic alignment of gallium nitride nanowires (GaN NWs) for use in device applications - Kim, T. H.; Lee, S. Y.; Cho, N. K.; Seong, H. K.; Choi, H. J.; Jung, S. W.; Lee, S. K. (IOP PUBLISHING LTD, 2006)
We report on a simple and effective ac and dc dielectrophoresis (DEP) method that can be used to align and manipulate semiconductor gallium nitride (GaN) nanowires (NWs) with variations in the type of electrical fields as well as variations of frequency. We observed that the ability of the alignment and the formation of the assembling nanowires (single or a bundle configuration) strongly depend on the magnitude of both the ac and dc electric fields. The yield results indicate that the GaN NWs, using ac DEP, are better aligned with a higher yield rate of approximately 80% over the entire array in the chip than by using dc DEP. In addition, we first demonstrated the simple hybrid p-n junction structures assembled by n-type GaN nanowires together with a p-type silicon substrate (n-GaN NW/p-Si substrate) using dielectrophoresis. From the transport measurements, the p-n junction structures show well-defined current rectifying behaviour with a low reverse leakage current of approximately 3 x 10(-4) A at -25 V. We believe that our unique p-n junction structures can be useful for electronic and optoelectronic nanodevices such as rectifiers and UV nano-LEDs.
Keywords: MANIPULATION; FABRICATION; DEPOSITION